The Impact of Talent Management and Job Rotation on Employee Engagement: The Role of Intrinsic Motivation - Widodo, Widodo; Nurhayati, Mafizatun; Pujiwati, Ami (International Journal of Management and Digital Business, 2024)
This study aims to analyze the influence of talent management and job rotation on employee engagement mediated by intrinsic motivation. The populations and samples taken were employees in staff positions within Yogyakarta Regional Tax Office with 230 respondents. This research used survey method with a closed questionnaire in the Google-form as research instrument and measured with Likert scale five points. The analysis method used is the Structural Equation Model – Partial Least Square (SEM-PLS) with the help of SmartPLS software version 3.2.9. The results show that talent management has a positive and significant effect on employee engagement. Talent management also has a positive and significant effect on intrinsic motivation. Intrinsic motivation has a positive and significant effect on employee engagement. Job rotation has a negative and significant effect on employee engagement. Job rotation has a positive and significant effect on intrinsic motivation. The role of intrinsic motivation in mediating the effect of talent management on employee engagement is included in partial mediation with the complementary mediation category. Intrinsic motivation also plays a role in mediating job rotation on employee engagement and is included in partial mediation with the competitive mediation category.